2019
DOI: 10.1093/cercor/bhz295
|View full text |Cite
|
Sign up to set email alerts
|

Up and Down States of Cortical Neurons in Focal Limbic Seizures

Abstract: Recent work suggests an important role for cortical–subcortical networks in seizure-related loss of consciousness. Temporal lobe seizures disrupt subcortical arousal systems, which may lead to depressed cortical function and loss of consciousness. Extracellular recordings show ictal neocortical slow waves at about 1 Hz, but it is not known whether these simply represent seizure propagation or alternatively deep sleep-like activity, which should include cortical neuronal Up and Down states. In this study, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Cortical neuronal recordings showed Up and Down states of action potential firing and membrane potential oscillations mimicking the physiology of deep sleep and anesthesia. [13][14][15][16]19,20 Why is cortical arousal depressed during focal limbic seizures? Human data showed altered activity in subcortical arousal areas such as the upper brainstem and thalamus (Figure 1B), leading to the network inhibition hypothesis.…”
Section: Network Inhibition Hypothesis and Other Mechanismsmentioning
confidence: 99%
“…Cortical neuronal recordings showed Up and Down states of action potential firing and membrane potential oscillations mimicking the physiology of deep sleep and anesthesia. [13][14][15][16]19,20 Why is cortical arousal depressed during focal limbic seizures? Human data showed altered activity in subcortical arousal areas such as the upper brainstem and thalamus (Figure 1B), leading to the network inhibition hypothesis.…”
Section: Network Inhibition Hypothesis and Other Mechanismsmentioning
confidence: 99%
“…Characteristics of focal limbic seizures, the type that most commonly affects consciousness, include (1) variable impairment in behavior, 9 (2) high‐amplitude delta oscillations in association cortices, 10 and (3) hemodynamic increases in upper brain stem/medial thalamus and decreases in association cortices 11 . The "network inhibition" hypothesis, 12 supported by evidence from our animal model work, 13,14 proposes that focal limbic seizures impair level of consciousness by inhibiting subcortical arousal systems, resulting in low‐frequency cortical oscillations 14–19 . However, our prior studies dissecting these mechanisms were performed under light anesthesia, which can affect electrophysiology and limit behavioral study.…”
Section: Introductionmentioning
confidence: 88%
“…At the cellular level, these oscillations are characterized by depolarized "Up" states and hyperpolarized "Down" states, with neurons in the Up state having increased firing rate and decreased input resistance. A few studies suggest that these states are also present in epileptic seizures that occur both in humans (38) and rodents (39), which is interesting, given that many seizure types also inhibit consciousness. One study using in vivo whole-cell recordings in a rat model of focal limbic seizures found that the membrane potential of frontal cortical secondary motor cortex layer 5 neurons oscillated during seizures and produced Up and Down states comparable to those seen during anesthesia (39).…”
Section: Time Of Day and Sleep/wake Effects On Seizures In Epilepsymentioning
confidence: 99%
“…A few studies suggest that these states are also present in epileptic seizures that occur both in humans (38) and rodents (39), which is interesting, given that many seizure types also inhibit consciousness. One study using in vivo whole-cell recordings in a rat model of focal limbic seizures found that the membrane potential of frontal cortical secondary motor cortex layer 5 neurons oscillated during seizures and produced Up and Down states comparable to those seen during anesthesia (39). Taken together, these findings shed light on mechanisms potentially linking sleep with certain types of seizures in epilepsy.…”
Section: Time Of Day and Sleep/wake Effects On Seizures In Epilepsymentioning
confidence: 99%